PERAN GURU AKIDAH AKHLAK DALAM MENANGGULANGI KENAKALAN SISWA DI MTS SYAFI'IYAH PULOREJO NGORO JOMBANG - NingSuryono, Adik Putra; Masruroh, Laily; Sa'diyah, Maidatus (PAI FAI UNHASY Tebuireng Jombang, 2025)
Degenerate behavior in the younger generation is largely a mistake in controlling oneself. Teachers and students have the greatest impact on delinquency because it occurs at the school level. The problem that is the subject of this research is student delinquency, which is a common occurrence in the world of education. Considering the problems above, this exploration has 3 objectives related to the central problem. The Tasks of Moral Aqidah Educators in Conquering Student Delinquency at Mts. Syafi'iyah Pulorejo Ngoro Jombang. The aim of this research is as follows: 1) To determine the forms of student delinquency at MTs Syafi'iyah Pulorejo. 2) To describe the factors that cause delinquency committed by students at MTs Syafi'iyah Pulorejo. 3) to describe how the MTs Syafi'iyah Pulorejo moral aqidah teacher handles student delinquency. This exploration is directed using a clear qualitative methodology. Interviews, observations, and written notes were used to collect data. Students, the Deputy Head of Student Affairs, and the Principal/moral aqidah teacher were informants in this research. The information gathered for perception and meetings is examined using in-depth methods, specifically reducing information, introducing information and reaching decisions. Based on research findings, some examples of student misbehavior include arriving late to school, chatting or being busy and chatting in class, dressing inappropriately, not respecting teachers, smoking, riding motorbikes to school, and truancy. Factors that cause student errors are family factors, school factors and social elements. Moral aqidah teachers use preventive, repressive, curative and rehabilitative strategies in dealing with this behavior.